Risk Factor Analysis on Drug Abuse Handled by National Narcotics Board of Republic of Indonesia in the Special Region of Yogyakarta during 2020 - Ida Bagus Gede Surya Putra Pidada; Wikan Basworo; Annastasia Octaviany Putrayasa (SOEPRA, 2021)
Abstract: Cases of drug abuse by various groups in Indonesia have a fairly high number. Especially in the Special Region of Yogyakarta in 2008 which was named the second-largest city in drug abuse. Many factors can cause a person to decide to become a drug user, both from individual factors and the environment. Based on individual factors, one of which includes sociodemographic status which is divided into age, gender, education level, and type of work. This study aims to describe the demographic risk factors that include age, gender, education level, and type of work on drug abuse. Statistical significance was analyzed using Pearson Chi-Square.From a total of 87 research subjects, it was found that almost all drug abusers were in the productive age, namely, 86 people (98,9%). The majority were male namely, 85 people (97,9%), more than half had high school education, namely 51 people (58,6%), and the majority of drug abusers were dominated by the student, namely 35 people (41,4%). The type of drug that is most widely used is the type of narcotics for as many as 61 people (70,1%). The relationship between sociodemographic characteristics and drug abuse itself had no significant results in the classification of age (p=0,699), gender (p=0,487), and type of work (p=0,254). Meanwhile, there were significant results for the level of education (p=0,027).Abstrak: Kasus penyalahgunaan narkoba oleh berbagai kalangan di Indonesia memiliki angka yang cukup tinggi. Khususnya di Daerah Istimewa Yogyakarta pada tahun 2008 yang dinobatkan sebagai kota terbesar kedua dalam penyalahgunaan Narkoba. Banyak faktor yang dapat menyebabkan seseorang memutuskan menjadi pengguna narkoba, baik dari faktor individu maupun dari lingkungan. Berdasarkan faktor individu, salah satunya meliputi status sosiodemografi yang didalamnya terbagi atas usia, jenis kelamin, tingkat pendidikan, dan jenis pekerjaan. Penelitian ini bertujuan untuk mengetahui gambaran faktor risiko demografis yang meliputi usia, jenis kelamin, tingkat pendidikan, dan jenis pekerjaan terhadap penyalahgunaan narkoba. Kemaknaan statistik dianalisis menggunakan Pearson chi-square.Dari total 87 subyek penelitian, didapatkan hampir seluruh penyalahguna narkoba berada pada usia produktif yaitu 86 orang (98,9%). Mayoritas adalah laki-laki yaitu 85 orang (97,9%), lebih dari separuh berpendidikan SMA yaitu 51 orang (58,6%), dan mayoritas penyalahguna narkoba di dominasi oleh anak sekolah yaitu 35 orang (41,4%). Untuk jenis narkoba yang paling banyak digunakan adalah jenis narkotika sebanyak 61 orang (70,1%). Hubungan karakteristik sosiodemografi dengan penyalahgunaan narkoba sendiri memiliki hasil tidak bermakna pada penggolongan usia (p=0,699), jenis kelamin (p=0,487), dan jenis pekerjaan (p=0,254). Sementara terdapat hasil yang bermakna pada tingkat pendidikan (p=0,027).